Position effects of letter priming on CVC word naming in adult speakers of English as second language - Varun Uthappa A G; Priyanka Shailat (Journal of All India Institute of Speech and Hearing, 2013)
The segmental overlap effects of intra-word constituents in naming CVC type of monosyllabic words by second language speakers of English has been established. However, the relative effect of position of the constituents when presented independently is not known. The present study investigated the effects of the initial, medial and final letter overlap on word naming in 30 second language speakers of English through a masked priming paradigm. The results revealed the presence of facilitation only by overlapping letters in the initial position, thereby signifying the role of ‘position’ in primed naming with overlapping components.